Nanocellulose Research Trends from Pineapple Plant Waste in Indonesia: Bibliometric Analysis Using VosViewer - Hariry, Amelia; Mardawati, Efri; Masruchin, Nanang (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The application of sustainable industry is carried out by utilizing pineapple plant waste by bibliometric and exploratory descriptive analysis using VOSviewer 1.6.18 software using a database of Scopus-indexed journal publishers. This study aimed to determine research trends on the utilization of pineapple plantation industry waste for nanocellulose production in Indonesia. The Scopus database collected information regarding Nanocellulose Research Trends From Pineapple Plant Waste. To obtain search results, subject categories with titles, keywords, and abstract criteria from Nanocellulose Research Trends From Pineapple Plant Waste were used as a reference. Using VOSviewer, search result extraction was performed. The results of bibliometric mapping were then further evaluated. The findings of the bibliometric study demonstrate through network visualization, overlay visualization, and density visualization that nanocellulose research in Indonesia has increased over the past seven years, beginning in 2015.